Tingkat Pengungkapan Islamic Social Reporting Pada Bank Syariah Di Indonesia Periode 2013-2015 - Norlaila Hayati (FAI, 2017)
Tingkat Pengungkapan Islamic Social Reporting Pada Bank Syariah Di Indonesia Periode 2013-2015